Pengaruh Belanja Modal, Belanja Pemeliharaan serta Belanja Barang dan Jasa Terhadap Realisasi Anggaran Pemerintah Desa - Rohmah, Nailatur; Wisdaningrum, Oktavima; Iswahyudi, M. (Al-Muhasib: Journal of Islamic Accounting and Finance, 2021)
This study aims to examine the effect of capital expenditure, maintenance expenditure, and goods and services expenditure on the realization of the village government budget. The basis of this research is Village Law No.6 which demands village transparency on the realization of the DD Budget to the community. The data used in this study are primary data using a questionnaire method. The object of this research is the village government in the electoral area II of the Banyuwangi Regency. The number of the objects of this research is 54 villages, and the respondents in this study are the village treasurers. The sample used is full sampling, where all populations are used as criteria and analyzed using classical assumption techniques, multiple linear regression analysis, and hypothesis testing. The results of this study partially with the test show that capital expenditure has a positive effect on the realization of orchids, maintenance expenditure has no effect on budget realization, and goods and services expenditures have no effect on budget realization, while simultaneously with the F test it shows that capital expenditure, expenditure Maintenance and Expenditures for Goods and Services affect the Budget Realization.